PENGARUH INTELLECTUAL CAPITAL, FINANCING TO DEPOSIT RATIO DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Hatta, Fakhri; Fitri, Fauziah Aida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This research aims to investigate the influence of Intellectual capital, Financing to deposit ratio and Non performing financing on profitability of Islamic Banking in Indonesia. The analysis technique used in this study is the multiple linear regression analysis. The type of data employed is secondary data from financial statements of each banks. The results of this research indicate that (1) Intellectual capital, Financing to deposit ratio and Non performing financing simultaneously effect on profitability (2) Intellectual capital has no significant effect on profitability (3) Financing to deposit ratio has significant effect on profitability and (4) Non performing financing has significant effect on profitability of Islamic Banking in Indonesia